ORAL HEALTH-RELATED QUALITY OF LIFE in CHILDREN AND ADOLESCENTS UNDERGOING ORTHODONTIC TREATMENT - Alice Chehab; Bogdan Radu Dragomir; Carina Balcos; Carmen Savin; Marius Bud; Irina Zetu (Romanian Society of Oral Rehabilitation, 2022)
Quality of Life (QoL) has an impact on the interaction and social integration of people, helping with self-confidence and well-being, which may or may not be influenced by the presence of malocclusions. Orthodontic treatment is the treatment of choice for dento-maxillary anomalies and as the latest data show, there is an increase in the number of people seeking fixed orthodontic treatment. To gain knowledge of the importance of orthodontic treatment and its impact on oral health-related quality of life (OHRQOL), we conducted a systematic review for evidence regarding the influence of orthodontic treatment on OHRQOL in children and adolescents.